Exploring the role of genome and structural ions in preventing viral capsid collapse during dehydration - Martín González, Natalia (2018)
Even though viruses evolve mainly in liquid milieu, their horizontal transmission routesoften include episodes of dry environment. Along their life cycle, some insect viruses, suchas viruses from the Dicistroviridae family, withstand dehydrated conditions with presentlyunknown consequences to their structural stability. Here, we use atomic force microscopy tomonitor the structural changes of viral particles of Triatoma virus (TrV) after desiccation. Ourresults demonstrate that TrV capsids preserve their genome inside, conserving their heightafter exposure to dehydrating conditions, which is in stark contrast with other viruses thatexpel their genome when desiccated. Moreover, empty capsids (without genome) resultedin collapsed particles after desiccation. We also explored the role of structural ions in thedehydration process of the virions (capsid containing genome) by chelating the accessiblecations from the external solvent milieu. We observed that ion suppression helps to keep thevirus height upon desiccation. Our results show that under drying conditions, the genomeof TrV prevents the capsid from collapsing during dehydration, while the structural ions areresponsible for promoting solvent exchange through the virion wall.